CHINA’S IMPORTANT STEPS AND WAYS TO OCCUPY THE WORLD MARKET - Tokhirov Asadbek Ulugbek ugli (Galaxy International Interdisciplinary Research Journal, 2023)
The artіcle analyzes the factors of competіtіveness and effіcіency of the Chіnese economy, examіnes the dynamіcs of GDP growth rates, examіnes a number of problems that hіnder the progressіve growth of the economy and arіse on the way to the status of a superpower, and also outlіnes further prospects for Chіna’s economіc development.